Sinergi Pelayanan Zakat dan Pajak Dalam Upaya Mengurangi Kemiskinan - Jumi Herlita (Alhadharah: Jurnal Ilmu Dakwah, 2017)
Zakat and taxes are two important sources of funding for the state. Both function to solve economic problems and reduce poverty in the community. But in reality the function of zakat and tax can not be optimal. BAZNAS and LAZ as an extension of the government in managing zakat can not be maximized in the collection of zakat funds as well as taxes. Although the nature of the tax is not specific to the poor, but also to the rich, but in fact the existence of taxes have not been able to solve poverty in Indonesia. Therefore it is necessary solution to synergize zakat and tax in order to increase zakat and tax collection. With bersinerginya zakat and taxes are expected to increase public awareness to pay zakat and taxes that can eventually be used to reduce poverty.